“What a Cliché, Right?” Insights from Mothers Opting for Part-Time Employment in Germany - Hertel, Irina (Socialinė teorija, empirija, politika ir praktika, 2025)
This narrative study explores the intersection of motherhood, employment choices, and care responsibilities in Germany. Despite its well-documented adverse effects on career progression, pension contribution, and risk of later-life poverty, two thirds of working mothers opt for part-time employment. However, qualitative research has yielded limited insights as to why mothers choose a particular employment model considering the heterogeneity of families in Germany. This contribution draws from a sample of 17 narrative interviews, comprising eight mothers born in Germany and nine born abroad. The narrative analytical approach according to Schütze was used to carry out the analysis. The study reveals that mothers’ employment decisions are shaped by a combination of personal preferences, structural constraints, and socio-economic factors. Mothers with higher education and previous full-time experience tend to pursue part-time work as a temporary compromise, often planning a return to full-time employment when family circumstances allow. However, those with limited qualifications or precarious legal and economic conditions face restricted labor market access, making part-time work less of a matter of choice and more a necessity driven by external pressures. Whether part-time work remains a career killer, a temporary option, or a personal choice, it transcends gender roles and delves into the individual biographies of mothers.